Resolution of mathematical problems mediated by reading comprehension - Alvarado Guerra, Pedro (2023)
Mathematics is one of the fundamental areas in the formation of human beings, not only in the very process of resolution of this exact science, but also in all areas of life; since its implementation in educational institutions, research has been carried out on how it can respond to global and national advances in the formation of competent citizens in different fields related to the consolidation of democratic values, which make it a primary reference in the educational policies of governments and school curricula. Currently, teaching methods in the field of mathematics have incorporated new relevant information, which leads to the construction of spaces where the teacher and the student interact to build knowledge that can be applied in different situations and contexts. This article refers to different research related to the importance of recognizing reading comprehension in the development of mathematical competencies. In order to develop the topic, a bibliographic search in databases was carried out, obtaining that reading comprehension is transversal to the curriculum, providing a series of basic knowledge in the interpretation of words and concepts necessary in the construction of the approaches required to achieve the expected results, allowing both teachers and students to advance significantly in the development of the solving process with verbal content.